9 - Enjeux de la pédagogie contrastée de l’histoire dans les sous-systèmes anglophone et francophone pour les politiques mémorielles au Cameroun - Ngo Nlend, Nadeige; Lado, Ludovic; Oukouomi, Gishleine; Etah, Ewane; Acha, Eric (Africa Development, 2022)
Based on the collection of empirical data in addition to documentary research, this article compares the teaching of the history of Cameroon in the French-speaking and English-speaking subsystems from the analysis of various educational and didactic materials. It questions Cameroon’s place in the historical discipline at the secondary level as well as the way in which certain aspects of its past are treated therein. While the first cycle history programs shared by the two subsystems do mention Cameroon at certain levels of education, the number of hours as well as the breadth of subjects covered are far higher in the English-speaking subsystem. Moreover, while history textbooks, assigned to the first cycle, in the Francophone subsystem overlook the themes relating to the construction of the State of Cameroon, all the Anglo-Saxon textbooks allocated to the first and second cycles devote large extracts to it. The article further probes the stakes of these disparities in the writing and teaching of the history of Cameroon in schools for the politics of memories at the national level. The article suggests for further investigation a close link between the pedagogy of history and identity politics in Cameroon.